Innovations in Local Public Transport – Significance for the Local Community - Trippner-Hrabi, Justyna; Podgórniak-Krzykacz, Aldona (European Spatial Research and Policy, 2018)
The article deals with the issues of the innovations implemented in public transport. Their theoretical background was defined in the form of the latest concepts of territorial development: the theory of sustainable development, circular economy, and smart city. The examples of innovations quoted above have been analysed in terms of their impact on: the local community, the environment, health, safety, and economic and social aspects. The main conclusion drawn from the analysis is that technical innovations in public transport contribute to improving mobility, the comfort and safety of commute, and, at the same time, have a positive impact on the environment.